IMPLEMENTATION OF THE THEORY MULTIPLE INTELLIGENCES IN IMPROVE COMPETENCE OF LEARNERS ON THE SUBJECTS OF ISLAMIC RELIGIOUS EDUCATION IN SMP NEGERI 14 AMBON - Mahatir Afandi Attamimi, Samad Umarella (al-Iltizam: Jurnal Pendidikan Agama Islam, 2019)
The purpose is to discover about Implementation Of Multiple Intelligences Theory to increase the ability of student in Islamic education’s subject of SMP Negeri 14 Ambon and to discover about supporting and obstacle factors of Implementation Of Multiple Intelligences Theory to increase the ability of student in Islamic education’s subject of SMP Negeri 14 Ambon. This research is using mixed method (qualitative facilitated by quantitative). The writer using observation, interview, documentation, and questionnaire to collect data. The results of this research has shown that Implementation Of Multiple Intelligences Theory to increase the ability of student in Islamic education’s subject of SMP Negeri 14 Ambon is greatly achieved. Proven with all activities like learning process and extracurricular programs in schools is already supported and developed the ninth intelligences. Although in developing process not all of that intelligences can perfectly achieved and not all that intelligences has achieved at the same time. The ninth intelligencesis linguistic-verbal intelligence, mathematiclogic intelligence, visual-spacial intelligence, kinesthetic intelligence, musical intelligence, interpersonal intelligence, intrapersonal intelligence, and existencial spiritual intelligence. The supporting factors of Multiple Intelligences Theory is suficient infrastructure facilities and teacher, good interaction within teacher and student, and great cooperation with public. Otherwise the obstacle factors of Multiple Intelligences Theory is less participation from parents, busy teacher, less information about intraschool competition’s events and the variance levels of student intelligences.